Impact of Artificial Intelligence and Digital Technologies on Consumer Behavior and Brand Perception: A Study of Young Consumers in Ahmedabad - Samsukha, Akshita; Trivedi, Pratham; Baldi, Vansh; Store, Shreyas; Naik, Pratham; Chauhan, Rahul; Maseleno, Andino; Raisa, Kharchenko (Greenation Research & Yayasan Global Resarch National, 2023)
This study investigates the impact of artificial intelligence (AI) and digital technologies on consumer behavior and brand perceptions among young consumers in Ahmedabad. Using a quantitative approach, data was collected from 116 respondents through a structured questionnaire to examine AI-driven personalized experiences such as product recommendations, virtual assistants, and their influence on consumer attitudes and purchase intentions. Statistical analysis revealed that AI integration significantly enhances consumer satisfaction and influences purchase decisions, while demographic factors such as gender and education showed minimal influence on AI preferences. The findings highlight the potential of AI to shape future consumer engagement and purchasing behavior. This research contributes to the understanding of AI's role in modern retail and its implications for businesses aiming to leverage AI for personalized marketing.